Obstructive sleep apnea prevents the expected difference in craniofacial growth of boys and girls - Juliano, Maria Ligia [UNIFESP] (2013)
OBJECTIVES: It was to compare cephalometric measures of mouth-breather boys and girls and with the cephalometric pattern observed in obstructive sleep apnea syndrome (OSAS) patients. METHODS: Craniofacial measurements of lateral cephalometric radiographs obtained from 144 children aged 7-14 years were compared between boys and girls, and both were compared to cephalometric pattern of OSAS patients. RESULTS: Mouth-breather boys and girls had no gender differences regarding to craniofacial morphology while nose-breather boys and girls showed those expected differences. Nose-breather boys presented a more retruded mandible and proinclined upper incisor when compared to nose-breather girls, but mouth-breather boys and girls had no differences. The measure NS.GoGn was the only variable with an interaction with gender and breathing. CONCLUSIONS: There were no cephalometric difference in mouth breather-boys and girls related to normal growth, suggesting that oral breathing make the same craniofacial morphology and both have craniofacial morphology close to that of OSAS patients.